ChemInform Abstract: Aldehyde as a Traceless Directing Group for Rh(III)‐Catalyzed C—H Activation: A Facile Access to Diverse Indolo[1, 2‐a]quinolines. Issue 44 (15th October 2015) - Liu, Xingyan; Li, Xiaoyu; Liu, Hu; Guo, Qiang; Lan, Jingbo; Wang, Ruilin; You, Jingsong
Abstract The transformation of N‐aryl indolyl aldehydes with symmetric 1, 2‐diaryl or 1, 2‐dialkylalkynes proceeds regioselectively and tolerates multiple functional groups including chloro, cyano, and methoxy carbonyl groups.